FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN MALNUTRISI PADA BALITA - Andi Lis Arming Gandini; Umi Kalsum; Sutrisno Sutrisno (Poltekkes Kemenkes Kalimantan Timur, 2016)
Malnutrition is a condition inadequate or excessive of nutrition. One of the way to improve health level is by correcting society nutritional status on toodler especially which is form age category prone to nutrient problems. This research conducted in community health centers of Mariam river working area, anggana sub-district, district of Kutai Kartanegara. With research quantitative method and descriptive analytic research design with cross sectional approach. Large samples in this research is all of toddler who have less of nutrient and malnutrition affordable that meet inclusion and exclusion criteria. Factors mother’s occupation status, mothers’s level education, food production, economy factor, food consumption factor, and utilization of health services categorical scale does chisquare analysis. As for results of multivariate analysis after controlled by variable number of children in family, family total in the house and mothers’s level education. There is relation between food consumption factor with toddler nutrition status it means that the unavailability of food by food production by family 16,2 times more likely to have toddler with malnutrition compared with productive family. Conclusion : children total factor, familiestotal, mother education, food consumption, economy, food production give contribution to the incidence malnutrition for toddler incommunity health centers of Mariam river working area, anggana sub-district, district of kutai kartanegara.